The Comparative Efficacy and Safety of Peginterferon Alpha-2a vs. 2b for the Treatment of Chronic HCV Infection: A Meta-Analysis - Alavian, Seyed Moayed (Kowsar, 2010)
BACKGROUND AND AIMS: Two types of peginterferon, alpha-2a (PEG-IFN-α2a) and 2b (PEG-IFN-α2b), are approved for the treatment of hepatitis C infection. Several high-quality studies have compared the efficacy of these two types of interferon, but it seems that any of these trials had inadequate statistical power on their own to find even a tiny difference between these two medicines. We pooled the available data in the literature to find any small difference between these two medicines. METHODS: In a systematic review of the literature, randomized controlled trials comparing the use of PEG-α2a vs. 2b were assessed. The DerSimonian and Laird method was employed to run meta-analysis. The end points were virological responses. RESULTS: In 7 randomized controlled trials, 3518 patients were randomized to receive PEG-IFN-α2a + ribavirin (n=1762) or PEG-IFN-α2b + ribavirin (n=1756). Early virological response (EVR), early treatment response (ETR), and sustained virological response (SVR) were greater for patients treated with PEG-IFN-α2a. Odds Ratios (ORs) were 1.38 (95% confidence interval [CI] 1.11-1.71), 1.67 (95% CI 1.24-2.24), and 1.38 (95% CI 1.02-1.88) respectively. In the subset of naïve patients with genotype 1/4 and 2, ORs of SVR were 1.38 (95% CI 1.02-1.88) and 4.06 (95% CI 1.67-9.86) respectively. PEG-IFN-α2a had significantly higher rate of neutropenia OR=1.50 (95% CI 1.25-1.79) but pooled OR for withdrawal rates was not significant [OR=0.78 (95% CI 0.47-1.29)]. CONCLUSIONS: PEG-IFN-α2a with similar safety is more effective than PEG-IFN-α2b. A longer duration of maximum serum concentration compared with PEG-IFN-α2b (168 vs. 48-72 h.) yields a greater SVR and higher neutropenia in PEG-IFN-α2a recipients.